2010
DOI: 10.1021/la1019422
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Chemistry on the Stability of Gold Nanostructures

Abstract: Understanding the role of surface chemistry in the stability of nanostructured noble-metal materials is important for many technological applications but experimentally difficult to access and thus little understood. To develop a fundamental understanding of the effect of surface chemistry on both the formation and stabilization of self-organized gold nanostructures, we performed a series of controlled-environment annealing experiments on nanoporous gold (np-Au) and ion-bombarded Au(111) single-crystal surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 43 publications
5
49
0
Order By: Relevance
“…However, the XPS data ( Fig. 6(d)) indicates that chemisorbed oxygen is dissociated after annealing at 200 • C. This is reasonably consistent with the reported decomposition temperature of the Au oxidized species at 150-200 • C [14,15]. The oxygen-depleted surface is much more reactive than the coordinated Au one, facilitating the growth of clusters or islands [25].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, the XPS data ( Fig. 6(d)) indicates that chemisorbed oxygen is dissociated after annealing at 200 • C. This is reasonably consistent with the reported decomposition temperature of the Au oxidized species at 150-200 • C [14,15]. The oxygen-depleted surface is much more reactive than the coordinated Au one, facilitating the growth of clusters or islands [25].…”
Section: Discussionsupporting
confidence: 84%
“…Thus, one would expect that the stability of NPG is strongly affected by the surface adsorbates [14][15][16], since the adsorbed species, such as oxygen, ozone, and carbon monoxide, can modify the surface diffusion. Biener et al [15] demonstrated that the surface chemistry could control the coarsening kinetics of NPG annealed in inert He and reactive O 3 environments. They found that the ligament size of NPG increased from 30 to 90 nm in He environment at 450 K, while conserved in reactive O 3 environment below the desorption temperature of oxygen (500 K).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the surface properties of nanoporous metals have big effects on the coarsening process. For example, the adsorbed oxygen [90] and coated thin TiO 2 film [91] on np-Au can greatly inhibit the coarsening of np-Au by slowing down the surface diffusivity of Au atoms. For nanoporous metals with an active property such as Ni, the annealing process should be carried out at a reductive atmosphere to convert the surface oxides.…”
Section: Ligament/pore Sizementioning
confidence: 99%
“…Snyder et al [69] and later others [70,75] have shown that the addition of Pt to the Au-Ag alloy can help to reduce coarsening and also enable smaller pore sizes to be obtained. Biener et al noted that adsorbed oxygen from ozone decomposition helps to stabilize the nanostructure against coarsening at low temperatures [115]. More recently, atomic layer deposition was used to form a very thin layer of Al 2 O 3 or TiO 2 on nanoporous gold, which helped to suppress coarsening and improve thermal stability [116].…”
Section: Specific Features Of Nanoporous Goldmentioning
confidence: 99%